The Role of Online Social Media to Support Seaweed Farmers in Indonesia: A Conflict Resolution Strategy - Pulubuhu, Dwia Aries Tina; Sutinah; Seniwati (International Journal of Criminology and Sociology, 2021)
The current study aims to introduce online social media to support seaweed farmers and as a conflict resolution strategy. Seaweed farmers have the power to develop seaweed because the product has a positive impact on the socioeconomic. This study observes the roles of online media in supporting seaweed production. This research found that an increase in seaweed production can improve the economic conditions of the community. The weaknesses of seaweed farmers are their low capital, low skills, low level of education, and low support for infrastructure. One skill required is the mastery of technology, especially online media. Online media are one of the vital tools that can help seaweed business processes. Therefore, seaweed farmers should know how to use online social media. The potential cultivation of seaweed is very much enhanced by a pattern of cooperation between seaweed farmers, other farmers, and other collaborations. The threats faced by the research area include the diminishing desire of the younger generation to cultivate seaweed, the very low skill related to using online social media, and extreme weather as an annual problem. We find that the role of online media is crucial to minimizing the risk factors for conflict.